Synthesis mechanism of carbon nanotube fibers using reactor design principles. (31st December 2018) - Lee, Sung-Hyun; Kim, Hye-Rim; Lee, Haemin; Lee, Jinwoo; Lee, Cheol-Hun; Lee, Jaegeun; Park, Junbeom; Lee, Kun-Hong
Graphical abstract: Highlights: Quality of the CNT fibers and continuity of the synthesis of CNT fibers were improved by applying reactor design principles. Identification of decomposition temperature and reaction sequence of chemicals in direct spinning process. Understanding on the effect of water on the decomposition of chemicals in the synthesis of CNT fibers. Increase of the quality of CNT fiber by controlling the injection position of water in the vertical reactor. Abstract: The direct spinning process is a useful method for continuously synthesizing carbon nanotube (CNT) fibers. A reactor should be designed based on reactor design principles in order to study the synthesis mechanism and mass production of CNT fibers. The internal temperature in a continuous flow reactor depends on the length of the reactor, and because the temperatures required for the decomposition of various feedstocks differ, each feedstock is decomposed at a different point in the reactor. Here, we report that high-quality CNT fibers were continuously synthesized by water injection at temperatures above the catalyst-forming range during the direct spinning process, as determined by the decomposition temperatures of the feedstocks. The decomposition temperatures of the feedstock materials were measured. Thiophene and toluene decomposed at 500–600 °C and 600–700 °C, respectively, and these temperatures were lower than those reported in the literature. The quality of the CNT fibers was improved by injecting water into zones with temperatures that exceeded the decomposition temperatures of the feedstocks in the reactor. Oxygen containing functional groups formed less often on the CNT surfaces, further improving the quality of CNT fibers. Moreover, the CNT fibers were continuously synthesized, even if excess water were injected.